2019
DOI: 10.4014/jmb.1810.10033
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase, Receptor Type B (PTPRB) Inhibits Brown Adipocyte Differentiation through Regulation of VEGFR2 Phosphorylation

Abstract: Brown adipocytes have an important role in the regulation of energy balance through uncoupling protein‐1 (UCP‐1)‐mediated nonshivering thermogenesis. Although brown adipocytes have been highlighted as a new therapeutic target for the treatment of metabolic diseases, such as obesity and type 2 diabetes in adult humans, the molecular mechanism underlying brown adipogenesis is not fully understood. We recently found that protein tyrosine phosphatase receptor type B (PTPRB) expression dramatically decreased during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The study of Kim et al showed ectopic over-expression of PTPRB inhibited the expression of adipocyte-related genes (such as PPAR-γ) and led to a reduced adipocyte differentiation from preadipocytes. Also, PTPRB was reported to suppress the tyrosine phosphorylation of VEGFR2 during adipocyte differentiation (Kim et al, 2019). Generally, VEGF functions by binding with VEGFR2, while transfection of VEGF to ASCs increased fat cell survival (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Kim et al showed ectopic over-expression of PTPRB inhibited the expression of adipocyte-related genes (such as PPAR-γ) and led to a reduced adipocyte differentiation from preadipocytes. Also, PTPRB was reported to suppress the tyrosine phosphorylation of VEGFR2 during adipocyte differentiation (Kim et al, 2019). Generally, VEGF functions by binding with VEGFR2, while transfection of VEGF to ASCs increased fat cell survival (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…PTPRB, a member of the protein tyrosine phosphatase (PTP) family, is an enzyme mainly expressed in endothelial cells essential for blood vessel remodeling and angiogenesis [ 49 ]. In ASCs, it has been linked to reduced adipocyte differentiation [ 52 ]. Moreover, the transcripts T-box transcription factor 1 (TBX1) and endothelial PAS domain-containing protein 1 (EPAS1) were identified, both giving rise to transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01119 might positively influence the transcription of protein tyrosine phosphatase receptor type B (PTPRB), which is involved in pathways that counteract adipose differentiation. In fact, PTPRB acts as a negative regulator of brown adipogenesis by suppressing the tyrosine phosphorylation of VEGFR2, and its expression decreases during BAT formation ( Kim et al, 2019 ). By interacting with its cognate ligand (VEGF), the VEGFR2 receptor has a major role in brown adipose tissue development and maintenance ( Bagchi et al, 2013 ).…”
Section: Lncrnas As Regulators Of Brown and Brite/beige Adipogenesismentioning
confidence: 99%